Bibliometric Analysis: The Potential of Beetroot (Beta vulgaris) for Diabetes Patients - Friska Feria Donza; Elsa Yuniarti (Jurnal Biologi Tropis, 2025)
This research aims to conduct a comprehensive bibliometric analysis of scientific publications on the potential of beetroot (Beta vulgaris) for diabetes patients. A quantitative method was employed by systematically collecting data from the Scopus database covering the period 2014-2023, using the specific keywords "Beta Vulgaris Or Beetroot and Diabetes or Blood and Sugar or Insulin". From the initial 153 indexed documents retrieved, 113 relevant articles were selected and subjected to detailed analysis. VOS Viewer software was utilized to generate network, overlay, and density visualizations, enabling exploration of complex relationships between publications, keywords, and research trends. The results reveal that publications can be categorized into two distinct clusters, with the most frequently occurring keywords being insulin, beetroot, metabolism, and Beta vulgaris. The year 2021 was identified as the peak period for research on beetroot's potential for diabetes management, indicating growing scientific interest in this area. This bibliometric analysis provides a valuable foundation for further development of evidence-based studies on the benefits of beetroot in diabetes management and opens avenues for innovative therapeutic approaches using this natural resource.